Digital Transformation, Disclosure Quality, and GreenInnovation: ‎What Does Board Independence Matter?‎ - Guo, Jia; Kassim, Aza Azlina Md (International Journal of Accounting and Economics Studies, 2025)
Environmental issues emerge due to rapid economic growth, and the Chinese government ‎responds to these issues by issuing environmental regulations and providing environmental ‎subsidies. In this case, corporations are under increasing pressure to change their production ‎and operation models. Based on this background, corporations need to integrate sustainable ‎practices into their operations, such as developing green innovation. In addition, digital ‎transformation has been recognized by corporations as a critical development direction. This ‎is attributed to the fact that digital technologies provide advanced tools and systems for ‎monitoring, reporting, and optimizing operations. These capabilities may improve the ‎operational efficiency of corporations, increase data transparency, and improve disclosure ‎quality, which appears to affect the development of green innovation. This research uses the ‎data of Chinese corporations to explore the impact of digital transformation on green ‎innovation, analyzes disclosure quality as a mediating mechanism, and emphasizes the role ‎of board independence‎.